2002
DOI: 10.2214/ajr.179.2.1790417
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hepatitis C Activity: Correlation with Lymphadenopathy on MR Imaging

Abstract: MR imaging depicts perihepatic lymph nodes in most patients with chronic hepatitis C. Lymph node number, size, and hyperintensity were related to the activity of chronic hepatitis C, but the results of liver function tests were not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
3
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
1
18
3
1
Order By: Relevance
“…25 Nodal sizes were also positively correlated with viremia 19,22 and could be markers for the virological response in the treatment of chronic hepatitis C. 29,32 However, they may be correlated with serological values that would consequently become controversial. 17,22,24,29 Our study demonstrated that different parameters of nodal size led to different results and that nodal width might be superior to other parameters in terms of representing a lymph node in its reactive state. Additional studies are needed to further elucidate this phenomenon.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…25 Nodal sizes were also positively correlated with viremia 19,22 and could be markers for the virological response in the treatment of chronic hepatitis C. 29,32 However, they may be correlated with serological values that would consequently become controversial. 17,22,24,29 Our study demonstrated that different parameters of nodal size led to different results and that nodal width might be superior to other parameters in terms of representing a lymph node in its reactive state. Additional studies are needed to further elucidate this phenomenon.…”
Section: Discussionmentioning
confidence: 80%
“…[16][17][18][19] Indeed, enlarged lymph nodes might be the only sonographic manifestation of significant liver disease. 10 Enlarged lymph nodes in the hepatoduodenal ligament have been reported in chronic hepatitis B 20,21 and in chronic hepatitis C, [16][17][18][19][22][23][24] with a variable incidence of 45-100%. Most studies performed before the era of hepatitis C virus (HCV) dealt with the nodal prevalence [8][9][10][11] ; studies performed after this era focused mainly on chronic hepatitis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, multiple non-invasive magnetic resonance imaging (MRI) and spectroscopy (MRS) procedures have been developed which yield a number of parameters characterizing diseased tissue. Using conventional MRI, some correlation was observed between lymph node number, size and hyperintensity, and the activity of chronic hepatitis C. 12 Another rapid MRI technique is diffusion-weighted imaging (DWI) which can be recorded in the liver within an apnea period. It measures the apparent diffusion coefficient (ADC) of water, a parameter dependent on the tissue structure.…”
mentioning
confidence: 99%
“…it has been reported that the lymph node size was correlated with an index of hepatocellular injury, aST, indices of cholestasis, alP and γ-GTP, and a humoral immune reaction marker, IgM level, and was a secondary reaction of inflammation in hepatic lobules (2). regarding cHc, lyttkens et al (1) reported a positive correlation between the ln index and γ-GTP (r=0.53), and Spinetti et al (8) reported a significant correlation with ALT, though no significant correlation with liver function was noted in other reports (5,15). Thus, the correlation between lymph node size and laboratory data was inconsistent among the previous reports, and the lymph node may be observed even in healthy individuals.…”
Section: Measurement No 8 Ln (Cut-off Value 70) --------------------mentioning
confidence: 93%